2020
DOI: 10.7759/cureus.9333
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic Steroids and Cardiovascular Outcomes: The Controversy

Abstract: Anabolic steroids (AS) are synthetic derivatives of the male sex hormone testosterone. The use of AS is not limited to bodybuilders and athletes, but non-athletes also use them. It is used to enhance athletic performance, induce muscle hypertrophy, and augment male sexual characteristics. AS use is associated with a wide range of side effects and potential cardiovascular complications. In this article, we have searched the available literature to investigate the association between AS use and cardiovascular di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 44 publications
1
30
0
3
Order By: Relevance
“…For instance, 15-60% of nutritional supplements were found to contain AAS when tested [35,36]. A recent review found a link between AAS and CVD risk factors, including hypertension or dyslipidemia, in seven of the nine studies reviewed [37], consistent with prior reviews [38][39][40][41]. Potential mechanisms underlying this link include increased systemic inflammation, oxidative stress, and vascular dysfunction [41].…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…For instance, 15-60% of nutritional supplements were found to contain AAS when tested [35,36]. A recent review found a link between AAS and CVD risk factors, including hypertension or dyslipidemia, in seven of the nine studies reviewed [37], consistent with prior reviews [38][39][40][41]. Potential mechanisms underlying this link include increased systemic inflammation, oxidative stress, and vascular dysfunction [41].…”
Section: Introductionsupporting
confidence: 59%
“…In sum, although preliminary research points to a prospective link between legal PES use and severe medical complications, there is a need to investigate long-term, prospective associations with specific health outcomes. In the present study, we focus on CVD risk factorsincluding diabetes, hypertension, abnormal lipid profiles, and obesity-in young adulthood given that these outcomes may take many years to fully manifest [38,42] and evidence suggesting that use of illegal PES (e.g., AAS) is associated with CVD risk factors [37][38][39][40][41]. Additionally, previous studies have been limited by small and/or highly specific samples (e.g., athletes) or comparison groups (e.g., vitamin users), warranting further evidence that large sample, population-based cohort studies are needed.…”
Section: Introductionmentioning
confidence: 99%
“…It also includes a direct effect on cardiac muscle metabolism, altering both electrical and structural features of the myocardium [ 44 ]. Supraphysiological doses of AASs induces toxicity of the CVS, with the proposed mechanisms including changes in the lipid profile, elevations in blood pressure, myocyte hypertrophy, disarray and apoptosis and a procoagulant state [ 45 ]. Thereby, contributing to disorders such coronary artery disease (CAD), hypertension, cardiomyopathy and thromboembolic disorders ( Figure 2 ); the above findings have been correlated with histopathological case reports [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…It also includes a direct effect on cardiac muscle metabolism, altering both electrical and structural features of the myocardium [30]. Supraphysiological doses of anabolic steroids induces toxicity of the cardiovascular system, with the proposed mechanisms including changes in the lipid profile, elevations in blood pressure, myocyte hypertrophy, disarray and apoptosis and a procoagulant state [31]. Thereby, contributing to disorders such coronary artery disease (CAD), hypertension, cardiomyopathy and thromboembolic disorders ( Figure 1); the above findings have been correlated with histopathological case reports [32,33].…”
Section: Steroid Pharmacology and Cardiac Physiologymentioning
confidence: 99%
“…Structurally, several modalities of dysfunction that may predispose to sudden cardiac death have been proposed that includes cardiac hypertrophy, ventricular dilatation, myocardial fibrosis and cardiomyopathy. There have been several case reports of young athletes that have developed rapidly progressive (dilated) cardiomyopathy [31]. Ventricular arrhythmias are another possibility, where it has been suggested that anabolic steroids inhibit the reuptake of catecholamines, and with a combination of exercise, stimulating the nervous system that may increase the likelihood of fatal arrhythmias.…”
Section: Role In Sudden Cardiac Deathmentioning
confidence: 99%